Trabalhando a arte de forma lúdica - Alves, Adair Rodrigues; Afonso , Jakelaine Gregorio; Alves , Joana Darc Xavier; Soares , Renaldo Ferreira; Oliveira , Wania Rosa Siqueira de (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf